2023
DOI: 10.3390/foods12234239
|View full text |Cite
|
Sign up to set email alerts
|

The Research Field of Meat Preservation: A Scientometric and Visualization Analysis Based on the Web of Science

Jingjing Zhang,
Zixiang Wei,
Ting Lu
et al.

Abstract: Meat plays a significant role in human diets, providing a rich source of high-quality protein. With advancements in technology, research in the field of meat preservation has been undergoing dynamic evolution. To gain insights into the development of this discipline, the study conducted an analysis and knowledge structure mapping of 1672 papers related to meat preservation research within the Web of Science Core Collection (WOSCC) spanning from 2001 to 2023. And using software tools such as VOSviewer 1.6.18 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…In summary, the visualization analysis of research institutions and countries indicated a close correlation between the volume of scientific literature and the distribution of I. verum resources. The tier of research journals serves as a critical instrument for gauging the quality of research [13]. Subsequently, we conducted a statistical analysis of the top 10 journals by publication count, both Chinese and internationally, with the results presented in Table 2.…”
Section: Countries and Institutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, the visualization analysis of research institutions and countries indicated a close correlation between the volume of scientific literature and the distribution of I. verum resources. The tier of research journals serves as a critical instrument for gauging the quality of research [13]. Subsequently, we conducted a statistical analysis of the top 10 journals by publication count, both Chinese and internationally, with the results presented in Table 2.…”
Section: Countries and Institutionsmentioning
confidence: 99%
“…Literature review is instrumental in understanding the cutting-edge developments within a field. However, the sheer volume of publications in databases presents a challenge in achieving a comprehensive grasp of the domain's evolution [12,13]. Traditional reviews often focus on a specific domain, and it is seldom feasible to encompass the entirety of the literature to analyze the current state of research within a particular field [13], thus necessitating more convenient methods for literature analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The meat processing stages are crucial for setting the groundwork for later procedures like chilling, chopping, and packing, including slaughtering and dressing. Meat processors may create premium meat products by ensuring animals are treated humanely, keeping environments clean, and using the right handling methods [64].…”
Section: Meat and Sausage Productsmentioning
confidence: 99%